Justice and Equity in Environmental Governance: A Socio-Ecological Sustainability Perspective - Saputra, Muhammad Fadhlan (Adaptive Governance Research, 2026)
Purpose: This study aims to examine justice and equity in environmental governance in East Kalimantan, Indonesia, using a social-ecological sustainability perspective. It focuses on the distribution of environmental benefits and burdens, the extent of public participation, the recognition of indigenous rights and local knowledge, and the integration of equity principles within sustainability-oriented policies. Subjects and Methods: The study employed a quantitative cross-sectional survey design involving 320 respondents from Samarinda, Balikpapan, Kutai Kartanegara, and Penajam Paser Utara. Data were collected using structured questionnaires and analyzed through SPSS 27 and Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4. Validity and reliability tests were conducted through convergent validity, discriminant validity, Cronbach’s Alpha, and Composite Reliability analysis. Results: The findings indicate that distributive justice, procedural justice, recognition justice, and equity-oriented governance significantly influence socio-ecological sustainability. Equity-oriented governance demonstrated the strongest effect on sustainability perceptions. Communities perceived environmental governance as insufficiently inclusive, participatory, and equitable, particularly regarding indigenous rights recognition and environmental benefit distribution. Governance inequalities were strongly associated with environmental vulnerability, declining ecosystem quality, and limited public participation. Conclusions: Justice-based environmental governance is essential for strengthening socio-ecological sustainability, institutional legitimacy, and inclusive environmental development in East Kalimantan.